YES Problem: f(s(x)) -> s(f(f(p(s(x))))) f(0()) -> 0() p(s(x)) -> x Proof: DP Processor: DPs: f#(s(x)) -> p#(s(x)) f#(s(x)) -> f#(p(s(x))) f#(s(x)) -> f#(f(p(s(x)))) TRS: f(s(x)) -> s(f(f(p(s(x))))) f(0()) -> 0() p(s(x)) -> x Matrix Interpretation Processor: dim=3 interpretation: [p#](x0) = [0 2 0]x0 + [2], [f#](x0) = [2 0 0]x0, [2] [0] = [0] [1], [0 1 0] [0] [p](x0) = [0 0 2]x0 + [1] [0 0 2] [2], [1 0 0] [f](x0) = [2 0 1]x0 [2 0 0] , [3 0 0] [2] [s](x0) = [1 0 0]x0 + [0] [0 1 1] [1] orientation: f#(s(x)) = [6 0 0]x + [4] >= [2 0 0]x + [2] = p#(s(x)) f#(s(x)) = [6 0 0]x + [4] >= [2 0 0]x = f#(p(s(x))) f#(s(x)) = [6 0 0]x + [4] >= [2 0 0]x = f#(f(p(s(x)))) [3 0 0] [2] [3 0 0] [2] f(s(x)) = [6 1 1]x + [5] >= [1 0 0]x + [0] = s(f(f(p(s(x))))) [6 0 0] [4] [6 0 0] [1] [2] [2] f(0()) = [5] >= [0] = 0() [4] [1] [1 0 0] [0] p(s(x)) = [0 2 2]x + [3] >= x = x [0 2 2] [4] problem: DPs: TRS: f(s(x)) -> s(f(f(p(s(x))))) f(0()) -> 0() p(s(x)) -> x Qed